2009
DOI: 10.1158/0008-5472.sabcs-701
|View full text |Cite
|
Sign up to set email alerts
|

Significant increased recurrence rates among breast cancer patients with HER2-positive, T1a,bN0M0 tumors.

Abstract: #701 Background: Controversy surrounds the prognosis of breast cancer patients with T1a,bN0M0 tumors following locoregional therapy and the need for adjuvant systemic therapy, especially for HER2+ disease. The purposes of the study were to determine the recurrence-free survival (RFS), and distant recurrence-free survival (DRFS) in small HER2+ tumors compared with hormone receptor ( HR)+ and triple receptor- (TN) tumors.
 Methods: Stage T1a,bN0M0 breast cancers diagnosed between 1973-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…HER-2 marker had predicting prognosis and outcome of breast cancer (Payne et al, 2008). HER-2 status was shown a significant predictor of disease-free survival in node -negative small size tumors (Rakkhit et al, 2009). High risk of relapse for patients who had HER-2 positive with node negative or small size tumor (Ana et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…HER-2 marker had predicting prognosis and outcome of breast cancer (Payne et al, 2008). HER-2 status was shown a significant predictor of disease-free survival in node -negative small size tumors (Rakkhit et al, 2009). High risk of relapse for patients who had HER-2 positive with node negative or small size tumor (Ana et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of over 2000 node-negative patients (Chia et al, 2008), HER2 status was shown to be an independent prognostic factor for disease-free survival in ER-negative patients. Rakkhit et al (2009) have shown HER2 to be a significant predictor of disease-free survival in a group of almost 1000 node-negative tumours o1 cm in size.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, including recent work by our group, have correlated biomarker status with rates of survival and distant recurrence (18). However, fewer studies have examined these biomarkers as predictors of locoregional recurrence (LRR).…”
Section: Introductionmentioning
confidence: 99%